2017
DOI: 10.1002/jcsm.12249
|View full text |Cite
|
Sign up to set email alerts
|

A muscle‐specific MuRF1‐E2 network requires stabilization of MuRF1‐E2 complexes by telethonin, a newly identified substrate

Abstract: BackgroundMuscle wasting is observed in the course of many diseases and also during physiological conditions (disuse, ageing). Skeletal muscle mass is largely controlled by the ubiquitin‐proteasome system and thus by the ubiquitinating enzymes (E2s and E3s) that target substrates for subsequent degradation. MuRF1 is the only E3 ubiquitin ligase known to target contractile proteins (α‐actin, myosins) during catabolic situations. However, MuRF1 depends on E2 ubiquitin‐conjugating enzymes for ubiquitin chain form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(73 citation statements)
references
References 65 publications
7
66
0
Order By: Relevance
“…MuRF1 targets like α‐actin, myosin heavy chains, and telethonin) and a repression of protein synthesis and anabolic factors (i.e. MAFbx targets like eIF3f and MyoD) are necessary for maintaining long‐term muscle atrophy . In our study, we also found that two other E3 ligases were up‐regulated at the mRNA level, that is, human double minute (Hdm2) and F‐box protein 30/muscle Ub ligase of the SCF complex in atrophy‐1 (Fbxo30/MUSA1).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…MuRF1 targets like α‐actin, myosin heavy chains, and telethonin) and a repression of protein synthesis and anabolic factors (i.e. MAFbx targets like eIF3f and MyoD) are necessary for maintaining long‐term muscle atrophy . In our study, we also found that two other E3 ligases were up‐regulated at the mRNA level, that is, human double minute (Hdm2) and F‐box protein 30/muscle Ub ligase of the SCF complex in atrophy‐1 (Fbxo30/MUSA1).…”
Section: Discussionsupporting
confidence: 61%
“…Indeed, none of the 20S and 19S RC subunits tested were up-regulated in both LC and HD patients at the mRNA levels, and only three of them were increased at the protein levels (Figure 1(C) and 1(D), Table 2, and Supporting Information, Table S1). E2 enzymes appeared also to be poor predictors of muscle atrophy in LC and HD patients (Figure 1(B) and Supporting Information, Table S1) in contrast with animal models in which UBE2B was considered as a bona fide atrogene and other E2s were often upregulated during catabolic situations (see Polge et al 41 for compiled data).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with this hypothesis and our previous report, a significant up‐regulated MuRF1 expression was evident in CHF, which was blunted by compound ID#704946. In line with the effect of compound ID#704946 on MuRF1 expression, also a trend towards a reduced expression of telethonin, a known substrate for MuRF1, was seen in CHF, which was also blunted in the compound‐treated group. To our surprise, we also detected a significant modulation of MuRF2 by compound ID#704946.…”
Section: Discussionmentioning
confidence: 99%
“…These miRs are similar to mRNA when first transcribed as primary RNA and are subsequently processed by the endoribonuclease DROSHA associated with PASHA to a precursor miR, which is further processed by the endoribonuclease DICER1 to form mature miRs. 5 Two key players of muscle wasting are the E3 ubiquitin ligases MAFbx and MuRF-1, the latter being the only E3 ubiquitin ligase known to target contractile proteins in catabolic conditions 6 and which can be inhibited by small molecules. 2,3 While some miRs are expressed ubiquitously in most tissues and cell types, other miRs are highly and specifically enriched in certain tissues.…”
Section: Introductionmentioning
confidence: 99%